Advanced Robust Disturbance Rejection Control Design for Quadrotor UAV Systems in Tracking Aggressive Trajectories - Nettari, Yakoub (Livre de Lyon, 2025)
This chapter analyzed the performance of Sliding Mode Control (SMC), Backstepping Control (BsC), and PID-based Sliding Mode Control (PIDSMC) for quadrotor trajectory tracking under constant and time-varying disturbances. Numerical simulations clearly demonstrated the superior performance of PIDSMC over the other methods. In Scenario 1, under constant disturbances, PIDSMC exhibited exceptional robustness and tracking accuracy, significantly outperforming SMC and BsC. While SMC maintained robustness but suffered from slow transitions, and BsC managed nonlinearities but lacked disturbance rejection, PIDSMC effectively combined these strengths. It ensured rapid response, minimized tracking error, and reduced chattering, leading to more stable and precise control. Scenario 2 further reinforced PIDSMC’s advantages in handling timevarying disturbances. It consistently maintained precise trajectory tracking despite dynamic external influences. Compared to SMC and BsC, PIDSMC exhibited superior disturbance rejection, faster convergence, and enhanced transient response, making it the most effective strategy for real-world quadrotor applications. Overall, PIDSMC not only integrates the robustness of SMC with the adaptability of PID but also offers smoother control inputs, improved stability, and superior trajectory tracking under diverse operating conditions. Its ability to handle complex disturbances while maintaining precision and efficiency makes it a highly promising approach for advanced UAV control. Future work may focus on further optimization and experimental validation to solidify its practical applicability.